2021
DOI: 10.3389/fimmu.2021.760288
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Correlates With Pronounced Aberrant Innate Immune Responses in Hospitalized Aged COVID-19 Patients

Abstract: Both age and obesity are leading risk factors for severe coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Specifically, although most infections occur in individuals under the age of 55 years, 95% of hospitalizations, admissions to the intensive care unit, and deaths occur in those over the age of 55 years. Moreover, hospitalized COVID-19 patients have a higher prevalence of obesity. It is generally believed that chronic low-grade inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 90 publications
(115 reference statements)
2
18
0
1
Order By: Relevance
“…The proinflammatory cytokines and chemokines, such as IL‐6, IL‐8, tumour necrosis factor (TNF), IL‐17, IL‐12, IL‐1, IP‐10, MCP‐1, and CCL5, were generally increased with higher BMI. 27 , 28 , 36 , 40 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 Furthermore, high levels of IL‐10, an anti‐inflammatory cytokine, appear to be a hallmark of hyperinflammation during severe SARS‐CoV‐2 infection, 57 , 58 and some studies included in this review observed that IL‐10 levels predict poor outcomes in COVID‐19 patients with obesity. 32 , 51 In an attempt to reduce the high COVID‐19 mortality rates due to a cytokine storm, intensive research is underway examining the use of anti‐inflammatory drugs.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…The proinflammatory cytokines and chemokines, such as IL‐6, IL‐8, tumour necrosis factor (TNF), IL‐17, IL‐12, IL‐1, IP‐10, MCP‐1, and CCL5, were generally increased with higher BMI. 27 , 28 , 36 , 40 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 Furthermore, high levels of IL‐10, an anti‐inflammatory cytokine, appear to be a hallmark of hyperinflammation during severe SARS‐CoV‐2 infection, 57 , 58 and some studies included in this review observed that IL‐10 levels predict poor outcomes in COVID‐19 patients with obesity. 32 , 51 In an attempt to reduce the high COVID‐19 mortality rates due to a cytokine storm, intensive research is underway examining the use of anti‐inflammatory drugs.…”
Section: Resultsmentioning
confidence: 87%
“… 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 Cell count of the innate immunity was altered in infected patients with a higher BMI in several studies. 29 , 33 , 34 , 35 , 36 The frequency of dendritic cells and monocytes was negatively correlated with BMI in aged COVID‐19 patients, 36 while natural killer (NK) cells decreased with BMI in young COVID‐19 patients. 36 In general, the neutrophil‐to‐lymphocyte ratio (NLR) is positively associated with adiposity and severity in COVID‐19‐positive patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations